ANALISIS PERAN STAKEHOLDERS DALAM PENGEMBANGAN OBJEK WISATA PANTAI KARANG JAHE DI KABUPATEN REMBANG - Fitri Handayani; Hardi Warsono (Journal of Public Policy and Management Review, 2017)
Tourism development aims to increase local revenue. One of the areas that conduct tourism development activities are Punjulharjo village. The potential Punjulharjo village is Karang Jahe beach that has its own uniqueness compared to other beaches in Rembang, therefore the development of tourism involves the role of stakeholders, including governments, local communities and the private sector. The purpose of this study to identify and analyze the role of stakeholders in developing the tourism Karang Jahe beach, the factors that inhibit the role of stakeholders in an effort to developing the tourism of Karang Jahe beach, and formulate efforts to solve the inhibit factors of stakeholders' role in developing the tourism of Karang Jahe beach in rembang district. The method is used qualitative descriptive. The results shows that tourism development Karang Jahe beach involves the role of Dinbudparpora, local communities, and businessmen. The roles ran by each of the stakeholders include policy creator, coordinators, facilitators, implementers and accelerator.The role of stakeholders in tourism development more emphasis on the role of facilitator in physical form. Factors that inhibit the role of stakeholders in tourism development of Karang Jahe Beach are limited land, limited budgets, limited human resources, mindset, regulatory, promotional activities, and cooperation among stakeholders. Efforts are being made to overcome the inhibit factors, namely make cooperation between the managers of Karang Jahe Beach with landowners, build the tourism awareness through the tourism awareness group, and empower villagers to utilize the waste into commercial product, sanctions are regulated in the village in terms of tourism business establishment, improvement Dinbudparpora website related to promotional activities attractions Karang Jahe Beach, as well as the need to do a binding cooperation between stakeholders support through a memorandum of agreement on cooperation.